Nanoporous GaN by selective area sublimation through an epitaxial nanomask: AlN versus SixNy. (11th June 2023) - Damilano, B; Vézian, S; Brault, J; Ruterana, P; Gil, B; Tchernycheva, M
Abstract: Nanoporous GaN layers were fabricated using selective area sublimation through a self-organized AlN nanomask in a molecular beam epitaxy reactor. The obtained pore morphology, density and size were measured using plan-view and cross-section scanning electron microscopy experiments. It was found that the porosity of the GaN layers could be adjusted from 0.04 to 0.9 by changing the AlN nanomask thickness and sublimation conditions. The room temperature photoluminescence properties as a function of the porosity were analysed. In particular, a strong improvement (>100) of the room temperature photoluminescence intensity was observed for porous GaN layers with a porosity in the 0.4–0.65 range. The characteristics of these porous layers were compared to those obtained with a Si x N y nanomask. Furthermore, the regrowth of p-type GaN on light emitting diode structures made porous by using either an AlN or a Si x N y nanomask were compared.